1993
DOI: 10.1073/pnas.90.17.7933
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated decreases in rRNA gene transcription factors and rRNA synthesis during muscle cell differentiation.

Abstract: ABSTRACTrRNA synthesis decreases significantly during the differentiation ofrat L6 myoblasts to myotubes. Nuclear run-on assays demonstrated that the decrease was attributable to decreased rates of rRNA gene transcription. Immunoblot analysis indicated a marked reduction in amounts of the RNA polymerase I transcription factors UBF1 and UBF2 (upstream binding factors 1 and 2, respectively). The levels of these factors dropped in parallel with the down-shift in rRNA gene transcription. The amount of UBF does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 34 publications
0
49
0
Order By: Relevance
“…We reported here that the amount of UBF is modulated during progression through interphase with a threefold increase in G2 compared with Gl. This increase in Sphase-G2 explains the progression of the amount of UBF found after 12 h of serum stimulation of starved cells (Cavanaugh et al, 1995), the time necessary for a majority of cells to reach S-phase-G2, whereas the low amount in differentiating cells (Larson et al, 1993) may reflect the amount of Go-G1 UBF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported here that the amount of UBF is modulated during progression through interphase with a threefold increase in G2 compared with Gl. This increase in Sphase-G2 explains the progression of the amount of UBF found after 12 h of serum stimulation of starved cells (Cavanaugh et al, 1995), the time necessary for a majority of cells to reach S-phase-G2, whereas the low amount in differentiating cells (Larson et al, 1993) may reflect the amount of Go-G1 UBF.…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly established that in deprived and growing cells, regulation of rRNA synthesis is under the control, at least in part, of UBF activity (O'Mahony et al, 1992;Glibetic et al, 1995). This activity can depend on the level of UBF phosphorylation (O'Mahony et al, 1992;Voit et al, 1992Voit et al, , 1995 and/or the amount of UBF (Larson et al, 1993;Glibetic et al, 1995;Hannan et al, 1995). The effect of stimulation or repression of the cell cycle on the amount of UBF is confirmed by the observation that the promoter of the UBF gene is regulated by growth-related control elements (Nishimura et al, 1994) and also by the fact that the UBF gene is a primary response gene to serum stimulation of cell growth (Glibetic et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrate quite clearly that rDNA transcription is regulated dierently depending on the stimuli evoking cell cycle arrest. Previous studies reported regulation of rDNA transcription during cell cycle arrest in response to various conditions such as nutritional deprivation, and stimuli that induced dierentiation and/or apoptosis (Cavanaugh et al, 1984(Cavanaugh et al, , 1995Mahajan and Thompson, 1990;O'Mahony et al, 1992;Larson et al, 1993;Paule, 1994;Moss and Stefanovsky, 1995). Under these conditions altering TFIC activity was attributed to be the major regulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…UBF content and phosphorylation In many cell lines, the amount of the transcription factor UBF is proportional to the rate of rDNA transcription (Larson et al, 1993;Hannan et al, , 1996b. In addition, overexpression of UBF is sucient to increase rDNA transcription from a co-transfected rDNA reporter construct (Hannan et al, 1996a, Figure 3 Cell cycle arrest is associated with minimal changes in RNA polymerase I content, PAF53 content, and TFIC activity.…”
Section: Paf53 Contentmentioning
confidence: 99%